2019
DOI: 10.1002/eco.2098
|View full text |Cite
|
Sign up to set email alerts
|

Estimating ecological flows for fish overwintering in plain rivers using a method based on water temperature and critical water depth

Abstract: Ecological flow is the foundation for conservation of riverine fish habitat and ecosystem. Habitat models have been widely used to estimate ecological flow owing to their integration of hydrological regime and species hydraulic preference. Previous studies based on habitat methods focused more on the spawning season but paid less attention to the winter period, which is also essential to fish life stage. This study developed a novel approach to estimate the ecological flow for fish overwintering, particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The ecological flow in plain rivers during overwintering period is difficult to be estimated by the habitat methods. Therefore, the water balance model (Wang et al, ) was adopted in this study. For comparison, the ecological flow regime by Tennant method was calculated and presented in Figure as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ecological flow in plain rivers during overwintering period is difficult to be estimated by the habitat methods. Therefore, the water balance model (Wang et al, ) was adopted in this study. For comparison, the ecological flow regime by Tennant method was calculated and presented in Figure as well.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the semi‐implicit Eulerian–Lagrangian finite‐element model was used for simulating hydrodynamic conditions in the study area (Wang et al, ). Through this model, the depth‐averaged flow velocity and the water‐surface elevation were computed by solving the shallow‐water equations, with hydrostatic and Boussinesq approximations (Zhang & Baptista, ).…”
Section: Methodsmentioning
confidence: 99%
“…Juveniles were seen to be more prone to the formation of aggregations than fish of older age groups. During the wintering season, the basic habitat requirements of other species of fish also shift to the most important aspects: sufficient depth and low flow rates (Mochek et al, 2019;Wang et al, 2019). In the study of riverbed depressions, it was shown (Mochek et al, 2015) that aggregations of fish in these water areas are also found during open-water periods.…”
Section: Discussionmentioning
confidence: 99%
“…In the lower reaches of the Irtysh River, there are wintering riverbed depressions with significant depths (> 35 m), which form on the meanders of the watercourse (Borisenko et al, 2013;Mochek et al, 2019). For fish, wintering is one of the critically important stages of their life cycle (Thayer et al, 2017;Wang et al, 2019;Studd et al, 2021;Sutton et al, 2021); in winter, juvenile fish have increased mortality compared to fish of older age groups (Deslauriers et al, 2018;Fernandes & McMeans, 2019;Takegaki & Takeshita, 2020). During this season, many species of fish (including sturgeons) prefer "temporal bottleneck" -wintering riverbed depressions (Thayer et al, 2017;Andrews et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the e-flow methods are relatively mature, and the classification of flow grading for different purposes is relatively precise in developed countries. Moreover, they focus on the minimum flow of rivers, as well as the need to gradually expand from the minimum flow to the level of current needs to maintain the institutional functions of river ecosystems, with particular attention paid to the flow required for spawning migration of in-channel organisms [19,20].…”
Section: Introductionmentioning
confidence: 99%